CAUGHT IN THE MIDDLE: AN AUTOETHNOGRAPHY OF LEADING AN EXTERNAL CAMPUS IN A STATE UNIVERSITY - Taha, Hanlie A. (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This autoethnographic study explores leadership in external campuses of a Philippine State University and College (SUC) system through my lived experiences across multiple administrative roles over two decades. Serving at different points as a founding campus director, campus director, dean of south campuses, and cluster dean, I experienced leadership from shifting positional vantage points within a multi-level governance structure marked by centralized authority, limited autonomy, resource scarcity, and overlapping jurisdictions. These roles allowed me to witness how policies are interpreted, negotiated, and enacted across institutional layers and local contexts. Using reflective narratives, memory work, and analytic memoing as primary sources of data, I examined how leadership is practiced in everyday administrative life. Five interrelated themes emerged: navigating multi-level governance and policy tensions; strategic adaptation and problem-solving leadership; relational leadership and stakeholder engagement; identity building and campus culture formation; and leadership resilience and professional wisdom. The findings reveal that leadership in external campuses is not merely administrative or procedural but deeply relational, adaptive, and symbolic. Directors function as boundary-spanning actors who translate centralized mandates into locally meaningful practices while sustaining institutional legitimacy and campus identity. By situating personal experience within broader organizational structures, this study contributes to higher education leadership and governance scholarship in the Philippine context. It demonstrates how leadership agency is exercised within bureaucratic constraints and underscores the importance of recognizing external campus leadership as central to equitable and inclusive higher education.